DISTRIBUTION AND ABUNDANCE OF AFRICAN LUNGFISH Protopterus annectens (OWEN, 1839) IN THE ORASHI AND SOMBREIRO RIVERS, NIGER DELTA, NIGERIA - FRANCIS, A; ONWUKA, C. N. (Nigerian Journal of Fisheries, 2021)
Studies on the distribution and abundance of the African lungfish Protopterus annectens in Orashi River and River Sombreiro were carried out between October 2013 and September 2014. Three hundred and forty-seven (347) specimens were sampled, made- up of one hundred and eighty-four (184) males and one hundred and sixty- three (163) females. The fish had an average length of 46.05 cm and an average weight of 140.75gm. The fish attained maximum growth both in length and weight 45.55 between April and July with mean length and weight of 45.55cm and 147.50gm respectively. The fish was most abundant between April and July which coincided with the rainy season, with values ranging between 10.95% and 11.24%. Monthly Catch per Unit Effort MCPUE ranged between 5.24kg/man/hour and 7.10kg/man/hour, with a mean value of MCPUE of 5.64kg/man/hr. The period April to July is the period of flood, and movement of debris and nutrients into the rivers, and discharge of human waste as food for the fish to support its growth, abundance, and distribution. The research underscores the need for a concerted effort towards conservation strategies to sustain the fish.